Pengaruh Model Pembelajaran Planted Question Terhadap Keaktifan Siswa Kelas IV SD Negeri 0104 Sibuhuan - Mancar; Lailan Aprina Siregar; Era Mutiah; Intan Amaliah (Journal Education Innovation (JEI), 2025)
This research aims to: (1) determine the effect of the planted question learning model on the activity of class IV students at SD Negeri 0104 Sibuhuan. The type of research used is quantitative research. This research was carried out in class IV of SD Negeri 0104 Sibuhuan. Subjects in class IV research at SD Negeri 0104 Sibuhuan. Data collection techniques in this research were obtained through questionnaires and documentation. The data analysis techniques in this research are validity and reliability testing, normality and homogeneity testing and hypothesis testing. Based on the research results, it can be concluded that there is an influence of the planted question learning model on the learning activity of class IV students at SD Negeri 0104 Sibuhuan, this can be seen in the students' pretest and posttest results. The average student score on the pretest was 29.82 and the average student score on the posttest was 32.68. The results of the hypothesis test obtained tcount = 1.664 while ttable = 1.008 (at the significance level a = 0.05). This means tcount > ttable = 1.664>1.008. In accordance with the basis for decision making, Ho is rejected, Ha is accepted, in the sense that there is an influence of the planted question learning model on students' active learning.